Opioid use and spinal cord stimulation therapy: The long game. (February 2021) - Hwang, Brian Y.; Negoita, Serban; Duy, Phan Q.; Tesay, Yohannes; Anderson, William S.
Highlights: Opioid dependence is a major problem in chronic pain patients. The effects of spinal cord stimulation (SCS) on opioid use in chronic low back pain remain controversial. We characterized long-term patterns of opioid usage after SCS implantation in patients who underwent device removal. Changes in opioid consumption were variable 1-year after implantation. Daily opioid use did not decrease in most patients 1-year after SCS implantation. Abstract: Spinal cord stimulation (SCS) has been considered as an alternative therapy to reduce opioid requirements in certain chronic pain disorders. However, information on long-term opioid consumption patterns and their impact on SCS device explantation is lacking. We conducted a retrospective study of 45 patients to characterize long-term patterns of opioid usage after SCS implantation. Daily morphine equivalent dosage (MED) increased, decreased, and remained the same in 40%, 40%, and 20% of patients at 1-year follow-up, respectively. Twelve (27%) underwent explantation due to treatment failure at a median of 18 months after implantation. Pre-operative opioid status (naïve vs. active use) was not associated with explantation (18% vs. 29%, p = 0.699) and neither was the daily MED change status (i.e. increased, decreased, unchanged) at 1-year (p = 0.499, 1.000, 0.735, respectively). Following explantation, reduction in the daily MED was seen in 92% of patients with dosages falling below pre-operative baseline in nine. Among the opioid naïve patients, 55% were on opioids at last follow-up (average 32.4 ± 14.6 months). Our results indicate that daily opioid consumption does not decrease in most patients 1-year after SCS implantation. Furthermore, post-operative evaluation beyond 1-year is necessary to assess the efficacy and durability of SCS therapy as well as its impact on opioid requirement. Lastly, rigorous patient selection and pre-operative risk assessment for misuse and dependence are paramount to improving outcome after SCS implantation.